Analysis of the Development of Indonesian Vocabulary Mastery of MI Nurul Huda Cipadung Kulon Bandung Students Grades 1-6: Analisis Perkembangan dalam Kemampuan Penguasaan Kosa Kata Bahasa Indonesia Siswa MI Nurul Huda Cipadung Kulon, Bandung Kelas 1 sampai Kelas 6 - Unnajjah, Shifaun (CV. Media Publikasi Profesional, 2024)
Children are the next generation of the nation that develops according to their respective stages of development. At the age of 6 to 12 years, which is included in the age of Primary School, they undergo rapid development, especially in the language aspect. This study aims to investigate the development of language in students in grades 1-6 in elementary school, in order to understand more deeply the process of language acquisition. Optimizing language development in children requires special attention from educators and parents, as this is an important achievement in their development. By exploring the way children speak, understand, and use language, this study seeks to fill the knowledge gap about the process of language development and provide insights to educators. The implication is that a learning approach is needed that is tailored to each stage of language development. Teachers play an important role in supporting students' language progress, helping them use Indonesian properly and correctly, and supporting their ability to organize themselves during the transition period. This research not only contributes to the development of teaching and education, but also suggests further research to explore more specific and effective learning strategies according to the stages of language growth. Support from schools and families is essential to creating a conducive learning environment, ensuring that every child can reach their full potential in language skills.